Co-Inoculation of Phosphate-Solubilizing Bacteria and Rhizobia Increases Phosphorus Availability and Promotes the Development of Forage Legumes - Winston Franz Ríos-Ruiz; Rony Castro-Tuanama; Renzo Alfredo Valdez-Nuñez; Lenin Torres-Bernal; Henry Giovani Jave-Concepción; Aurora Consuelo Daza-Pérez; Marvin Barrera-Lozano; Fernando Archentti-Reátegui (Agronomy)
Tropical grassland soils, especially those with alkaline properties, often exhibit limited phosphorus availability due to its precipitation in insoluble forms. Phosphate-solubilizing bacteria (PSB) and rhizobia have demonstrated their potential to enhance the availability of this nutrient and promote the growth of forage legumes. This study, conducted under controlled conditions in a mesh house, evaluated the effect of co-inoculation with PSB, including Micrococcus sp. Sfcm-14-01, Agrobacterium sp. Sfl-043-09, and Enterobacter sp. Sfcm-014-02 and Sfcm-054-06, along with rhizobia (Ensifer terangae R1-012-02 and Bradyrhizobium glycinis Rcm-025-01), under different levels of phosphorus fertilization on the legumes Leucaena leucocephala and Centrosema macrocarpum. The results indicate significant increases in various growth parameters, such as chlorophyll levels (SPAD), biomass (dry weight of roots and aerial parts) (mg), the foliar phosphorus concentration (ppm), and the concentration of available phosphorus in the soil, particularly under low-phosphorus fertilization conditions. The highest level of available phosphorus in the soil was achieved with 75% of the recommended fertilization dose, resulting in concentrations of 13.73 ppm for L. leucocephala and 7.69 ppm for C. macrocarpum, representing increases in phosphorus availability of 170.81% and 240.27%, respectively, compared with no fertilization or inoculation. These findings suggest that the co-inoculation of PSB and native rhizobia is a promising strategy to enhance the biomass productivity and mineral content of forage in tropical grazing systems, especially under phosphorus-limited conditions.